2019
DOI: 10.1002/pam.22155
|View full text |Cite
|
Sign up to set email alerts
|

Can Light‐Touch College‐Going Interventions Make a Difference? Evidence from a Statewide Experiment in Michigan

Abstract: I conduct a statewide experiment in Michigan with nearly 50,000 high-achieving high school seniors. Treated students are mailed a letter encouraging them to consider college and providing them with the web address of a college information website. I find that very high-achieving, low-income students, and very high-achieving, minority students are the most likely to navigate to the website. Small changes to letter content affect take-up. For example, highlighting college affordability induces 18 percent more st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 38 publications
2
32
0
Order By: Relevance
“…Overall, the results of this experiment do not suggest that strategic framing of informational messages is appreciably more effective than providing informational text messages at all. This is consistent with the mixed evidence in studies that have compared the relative efficacy of behavioral frames in text messaging interventions, as well as the null effects found in other studies that have taken text messaging interventions to state and national scale (e.g., Bird et al, 2019; Gurantz et al, 2019; Hyman, 2020). The mixed results in the literature raise questions regarding the way in which informational interventions are personalized and by whom they are delivered.…”
Section: Discussionsupporting
confidence: 88%
“…Overall, the results of this experiment do not suggest that strategic framing of informational messages is appreciably more effective than providing informational text messages at all. This is consistent with the mixed evidence in studies that have compared the relative efficacy of behavioral frames in text messaging interventions, as well as the null effects found in other studies that have taken text messaging interventions to state and national scale (e.g., Bird et al, 2019; Gurantz et al, 2019; Hyman, 2020). The mixed results in the literature raise questions regarding the way in which informational interventions are personalized and by whom they are delivered.…”
Section: Discussionsupporting
confidence: 88%
“…The magnitudes of these effects are much larger than those in previous interventions with similar goals (Hoxby and Turner 2013;Bettinger et al 2012;Goldrick-Rab et al 2016;Bergman, Denning and Manoli 2017;Oreopoulos and Ford 2019;Gurantz et al 2019;Hyman 2019). Several dimensions of the HAIL intervention set it apart, and plausibly explain the size of its effect.…”
Section: Michiganmentioning
confidence: 82%
“…Castleman et al (2014) found that contacting high school graduates via phone, email, and text messaging increased the likelihood of college enrollment among Hispanic males. Hyman (2020) mailed letters encouraging high-achieving high school seniors to consider college and engage with a custom website containing additional information. The author reported that low-income students were more likely to attend college after receiving the informational letters, but the results appeared to be driven by low-income student enrollment at 4-year institutions.…”
Section: Literature Reviewmentioning
confidence: 99%